DETEKSI CEMARAN Salmonella Sp. PADA IKAN BANDENG (Chanos chanos) DI PASAR IKAN SIDOARJO - Freshinta Jellia Wibisono (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2019)
Salmonellosis is one of foodborne disease. Milkfish is very susceptible to contamination of Salmonella Sp bacteria. Which can be transmitted to humans. Microbiological testing is one of the indicators on the examination of contamination. The main factor causing the contamination could be the presence of pathogenic bacteria found in foodstuffs. The purpose of this study was to detect contamination of Salmonella Sp. In milkfish (Chanos chanos) in Sidoarjo Fish Market using checking indicator using media for SSA and TSIA. The results showed that there were 20 samples from a total of 42 milkfish taken from the fish market was positive for Salmonella sp bacteria. This positive detection indicates the height of its contamination that can lead to the transmission of disease in humans.